2009
DOI: 10.1590/s0102-33062009000100029
|View full text |Cite
|
Sign up to set email alerts
|

In vitro morphogenesis and cell suspension culture establishment in Piper solmsianum C. DC. (Piperaceae)

Abstract: RESUMO -(Morfogênese in vitro e estabelecimento de culturas de suspensão celular em Piper solmsianum C. DC. (Piperaceae)). Piper solmsianum é uma espécie herbácea do sudeste brasileiro onde vários compostos biologicamente ativos já foram identificados. O objetivo deste trabalho foi estabelecer suspensões celulares nesta espécie. Para tanto, foram utilizados explantes de pecíolos e folhas, retirados de plântulas cultivadas in vitro, os quais foram submetidos a diferentes combinações de reguladores de cresciment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(29 reference statements)
1
10
0
1
Order By: Relevance
“…Leaf explants were individually transferred with the adaxial surface up, to test tubes (25 mm x 150 mm) containing 10 mL of an MS (Murashige & Skoog, 1962) basal culture medium supplemented with 3% (w/v) sucrose, 0.6% (w/v) agar and factorial combinations of 2,4-Dichlorophenoxyacetic acid (2,4-D) (0, 4.52, 9.05, or 18.10 µM) and 6-Benzylaminopurine (BA) (0, 4.44, 8.88, or 17.76 (Table 1) each one with three replicates of three explants. The growth regulators, their concentrations and combinations tested were based on successful studies on callus induction in Piper species; P. cernuum, P. crassinervum (Danelutte et al, 2005), P. solmsianum (Balbuena et al, 2009), P. aduncum (Delgado-Paredes et al, 2013), and P. hispidinervum (Santiago, 2013). The pH of the medium was adjusted to 5.8 before the addition of agar followed by autoclaving at 121°C for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaf explants were individually transferred with the adaxial surface up, to test tubes (25 mm x 150 mm) containing 10 mL of an MS (Murashige & Skoog, 1962) basal culture medium supplemented with 3% (w/v) sucrose, 0.6% (w/v) agar and factorial combinations of 2,4-Dichlorophenoxyacetic acid (2,4-D) (0, 4.52, 9.05, or 18.10 µM) and 6-Benzylaminopurine (BA) (0, 4.44, 8.88, or 17.76 (Table 1) each one with three replicates of three explants. The growth regulators, their concentrations and combinations tested were based on successful studies on callus induction in Piper species; P. cernuum, P. crassinervum (Danelutte et al, 2005), P. solmsianum (Balbuena et al, 2009), P. aduncum (Delgado-Paredes et al, 2013), and P. hispidinervum (Santiago, 2013). The pH of the medium was adjusted to 5.8 before the addition of agar followed by autoclaving at 121°C for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Valle (2003), studying the callus growth of the same species observed the deceleration phase starting on the 40 th day. Balbuena et al (2009) used callus cells of P. solmsianum on the 24 th day of culture to initiate cell suspension cultures. The appropriate time to subculture the calluses of P. permucronatum in order to establish cell suspension cultures is in the beginning of the deceleration phase, on the 56 th day of culture, when the cells have to be transferred to a new culture medium due to the reduction of nutrients, agar dryness and accumulation of toxic substances.…”
Section: Callus Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few chemical or biological aspects of this plant have been investigated. Phytochemical studies of this species indicate the presence of aliphatic hydrocarbons, monoterpenes, sesquiterpenes, arylpropanoids and neolignans [9][10][11][12]. Moreira and coworkers [9,11] demonstrated that the essential oil from this plant has promising depressant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Las ventajas de emplear biotécnicas en la producción de plantas de uso medicinal, respecto a la producción por agricultura tradicional son (Karuppusamy, S., 2009;Al-Sane, K. O. et al, 2005;Balbuena, T. S. et al, 2009):…”
Section: Producción De Metabolitos Secundarios Por Cultivo In Vitrounclassified